Factors associated with health-related quality of life of breast cancer patients in a tertiary hospital in Albania - Irsida Mehmeti; Edmond Zaimi; Elizana Petrela (Journal of Education and Health Promotion)
BACKGROUND: Breast cancer (BC) is the leading cause of cancer deaths in Albanian women, accounting for about 6.3% of total cancer deaths. The main objective of this study is to highlight the health-related quality of life (QoL) scale scores for Albanian women in stable clinical conditions with BC. MATERIALS AND METHODS: For this study, the European Organization for Research and Treatment of Cancer Quality of Life (EORTC QLQ – C30) questionnaire was used. Data were analyzed by the Statistical Package for Social Sciences, version 15 for Windows (SPSS Inc., Chicago, Illinois). For the functional scales and global QoL, a higher score corresponds to better functioning and QoL, while for symptom scales, a higher score corresponds to more frequent and/or more intense symptoms. RESULTS: In total, 51 women participated in the study. The mean age was 57.2 years old (SD = 11.1). Of the QLQ–C30 scales, the patients seemed to perform averagely too well on both the symptom scales and the functional health status scales. Of the functional scales, the mean score for the global QoL scale was 67.2%±20.3, while the range of mean scores for the five scales was from 53.6% to 73.5%, indicating a predominantly average level of general well-being with a good level of functional health status. CONCLUSION: Despite the progress made, Albania faces challenges in implementing international guidelines on cancer management. Despite institutional support, cancer is associated with significant financial burdens.